Actor dynamics in farmland protection: A MACTOR analysis in Tasikmalaya, Indonesia - Faqihuddin, Faqihuddin; Soedarto, Teguh; Hendrarini, Hamidah; Mubarokah, Mubarokah (Asian Journal of Agriculture and Rural Development, 2025)
Agricultural land protection is vital for ensuring food security, especially in peri-urban areas of developing countries facing rapid urbanization and land conversion. This study analyzes actor interactions in implementing Sustainable Food Agriculture Land (SFAL) Protection in Tasikmalaya City, Indonesia, using the MACTOR (Matrix of Alliances and Conflicts: Tactics, Objectives, and Recommendations) method. The use of MACTOR in farmland protection in Indonesia is still limited. The study provides a novel approach to uncover alliances, conflicts, and power asymmetries among policy actors. Data were collected through focus group discussions and in-depth interviews with stakeholders from government institutions, farmer organizations, and the private sector. The analysis identified eleven key actors and six strategic objectives, including regional regulation, soil fertility, irrigation management, cost-efficient farming, and livelihood diversification. Results show that private developers exert the greatest influence, followed by the city government through the Regional Development Planning Agency, sub-district authorities, and the Mayor. In contrast, farmers and their groups remain marginalized with limited policy influence. Despite this, there is formal alignment among actors toward land protection goals. The study highlights the need to strengthen farmer institutions, enhance transparent land governance, and develop multi-actor collaboration to balance agricultural sustainability and urban growth pressures.